OS SIGNOS DO ZODÍACO NA CERÂMICA DE LYNDHA FERNANDES - LYNDHA FERNANDES FRANCO (2024)
This final graduation project, presented to the Bachelor's Degree in Visual Arts program, aims to produce ceramic works based on the personal experience and interpretation of each zodiac sign: Aries, Taurus, Gemini, Cancer, Leo, Virgo, Libra, Scorpio, Sagittarius, Capricorn, Aquarius, and Pisces. A total of 12 signs were represented through ceramic pieces, each embodying a set of characteristics that can be artistically explored. The entire production used chamotte ivory clay, and the modeling process involved tools such as gouges, modeling tools, guides, wooden rollers, and brushes. Ceramics, as an artistic expression, goes beyond the creation of utilitarian objects, delving into the construction of meanings while aesthetically exploring the artist's subjectivity. Throughout this project, ceramics are presented not only as a material but also as a form of visual communication. The work draws on the technical and practical studies of artist, writer, and professor Peter Cosentino, alongside the contributions of writer and ceramist Emmanuel Cooper, who explores the history and contemporary practices of ceramics. As a result, this project presents a collection of visual interpretations of the zodiac signs, emphasizing the intersection between artistic language and the symbolic codes associated with astrology. The series demonstrates how abstract concepts can be translated into three-dimensional forms through ceramics, employing manual techniques and finishes that highlight the visual and textural elements of each sign. This approach significantly contributes to the field of Visual Arts by providing a technical and conceptual example of how symbolic themes can be transformed into artistic works, expanding the repertoire of languages and creative processes.